Application Service Provision (ASP) for e-business transformation by SMEs. (15th January 2007) - Seltsikas, Philip; Brown, Lisa K.
This paper examines the deployment of web-based technologies and business services as strategic e-business instruments by Small- and Medium-sized Enterprises (SMEs) in an attempt to revolutionise how they trade and interact with each other and with their customers. SMEs are increasingly seeking to enhance existing business processes, especially since such emerging technologies have transformed themselves from information and research tools, into exploitable business mechanism for increasing desired business benefits including customer awareness and sustained competitive advantage. The research presented in this paper investigates outsourced technology offering to SMEs by Application Service Providers (ASPs manage and deliver application capabilities to multiple entities from data centres across wide area networks, delivering applications using web-based technologies usually for a monthly fee) whilst outlining the position of the ASP market. It also discusses why some SMEs may or may not prefer to outsource their traditional/e-business processes via an ASP to facilitate the e-business transition.